KEPEMIMPINAN KEPALA MADRASAH DI LEMBAGA PENDIDIKAN ISLAM - Murni Murni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Leadership is a series of activities to influence others in achieving certain goals. Achieving goals in an organization are very dependent on the leadership used by the leader, this shows that leadership includes at least three which are interconnected, namely the existence of followers, the existence of group situations, and members interacting with each other. The principal of madrasah is the key to the success and progress of improving the quality of madrasah. Because madrasah is an educational institution organization in which it must have a qualified leader. A quality leader will be able to bring the madrasah towards the goals it is trying to achieve and be able to overcome the various obstacles it faces. In Islamic education institutions, namely schools, the head of the madrasah will bring the madrasah to the goal of achieving the quality of the madrasah according to what has been targeted.